Effect Crud alkaloids extraction from Nicotina tabacum in same cell line: Efek Ekstraksi alkaloid kasar dari Nicotina tabacum dalam garis sel yang sama - abood, Raghad Hussein; Mohammed, Ibrahim Hadi (Universitas Muhammadiyah Sidoarjo, 2025)
This study aimed to investigate some Chemical Detections of Some Compounds Nicotina tabacum in leaves of plant and the effects of the crude alkaloid extraction from Nicotina tabacum on the proliferation of MCF7 cancer cell line and MEF normal cell line. The Results the plant extraction showing alkaloid , Tannins and glycoside .the effect extract on growth of tumor cell lines MCF7 showed that crude extract revealed cytotoxicity on different cell line, and this effect depend on concentration and type of cells. The inhibition activity for tumor cell line increase with increase concentration of extract. The higher inhibition crud extraction rate in MCF7 cell line was % in concentration 15.1 µgand in 500 µ gwas %, While in MEF cell line, the highest inhibition rate was % in 15.1 µ gand % in concentration 500 µ g. The study shows that crude alkaloids extract Nicotina tabacum have alkaloid and inhibition cell line and non inhibition normal cell.Highlight : Crude alkaloid extract from Nicotiana tabacum inhibited MCF-7 breast cancer cells in a dose-dependent manner. MEF normal cells showed minimal sensitivity, indicating selective cytotoxicity. Phytochemical screening confirmed the presence of alkaloids, flavonoids, tannins, and glycosides as active compounds. Keywords : Nicotiana Tabacum, Alkaloids, MCF-7, Cytotoxicity, Selective Inhibition